Health-seeking behaviour during times of illness among urban poor women: a cross-sectional study - Khadijahtul Qubra Amizah Hamzah; Nor Afiah Mohd Zulkefli; Norliza Ahmad (BMC, 2024)
Abstract Background Urban poor women face dual challenges regarding gender inequalities and urban poverty, which make them more likely to have health problems and affect their health-seeking behaviour. This study aimed to determine the prevalence of health-seeking behaviour during times of illness and predictors of sought care among urban poor women in Kuala Lumpur, Malaysia. Methods This cross-sectional study was performed among 340 randomly selected women residents from April to May 2023. Data was collected using a validated and reliable self-administered questionnaire and analysed using SPSS version 28.0 software. The dependent variable in this study was health-seeking behaviour during times of illness, while the independent variables were sociodemographic characteristics, socioeconomic characteristics, medical conditions, women's autonomy in decision-making, social support, perceived stigma, and attitude towards health. Multiple logistic regression was used to identify the predictors of sought care during times of illness. Results Study response rate was 100%, where 72.4% sought care during times of illness. Being non-Malay (AOR = 4.33, 95% CI: 1.847, 10.161), having healthcare coverage (AOR = 2.60, 95% CI: 1.466, 4.612), rating their health as good (AOR = 1.87, 95% CI: 1.119, 3.118), and having pre-existing chronic diseases (AOR = 1.92, 95% CI: 1.130, 3.271) were identified as predictors of sought care during times of illness. Conclusion The present study showed that health-seeking behaviour during times of illness among the participants was appropriate. Health promotion and education, with a focus on educating and raising awareness about the importance of seeking timely healthcare, are crucial to improving health-seeking behaviour among urban poor women. Collaboration with relevant stakeholders is needed to develop comprehensive strategies to improve access to healthcare facilities for these women.